Effectiveness of Direct Application of Phosphate Rock in Upland Acid Inceptisols Soils on Available-P and Maize Yield - . Nurjaya; Dedi Nursyamsi (JOURNAL OF TROPICAL SOILS, 2013)
Source of P fertilizer which is used by farmers in upland acid soils area is generally acidulated phosphate rock (PR), such as tripel super phosphate (TSP), super phosphate 36% P2O5 (SP-36), as well as partial acidulated phosphate rock (PAPR) which contain 10-30% P2O5. Their effectiveness, however, varies and depends on the soil and plant types. Phosphate rock fertilizers have a high prospects for acid soils because its effectiveness equals to the SP-36, cheaper, slow release, and its application can also leave  the residual P in the soil that available for plants for next few seasons. Field experiment aimed to study the effectiveness of direct application of PR at upland acid soils and its effect on soil available-P as well as maize (Zea mays L.) yield was conducted in Acid Inceptisols of Ciampea, Bogor in wet season years 2008/2009. The experiment was arranged by a Randomized Completely Block Design with 3 replications. Maize of P-12 variety was used as a plant indicator. The treatment consisted of 6 levels of phosphate rock: 0, 20, 30, 40, 50, and 60 kg P ha-1, as well as one level of SP-36 40 kg P ha-1 as standard fertilizer. In addition, urea of 300 kg ha-1 and KCl of 100 kg ha-1 were used as basal fertilization. The result showed that the application of PR in the amount ranging from 20 to 60 kg P ha-1 increased total-P and available-P, and pH, decreased exchangeable Al in the soils as well as increased maize straw and grain. Phosphate rock  application at 40 kg P ha-1 level was equally effective as SP-36 in the tested soils. Critical level of soil P for maize grown in the soil was 675 and 5.00 mg P2O5 kg-1 extracted with HCl 25% and Bray I, respectively. The requirement of P for maize grown in the soil to achieve maximum profit was 38 kg P ha-1 and 17.5 kg P  ha-1 or equivalent to PR of 583 and 268 kg ha-1 in low (soil P < critical level) and high (soil P > critical level) soil P status,  respectively.Keywords: Direct application, phosphate rock, soil available-P, upland acid soils.[How to Cite: Nurjaya and D Nursyamsi. 2013. Effectiveness of Direct Application of Phosphate Rock in Upland Acid Inceptisols Soils on Available-P and Maize Yield. J Trop Soils 18 (1): 1-9. doi: 10.5400/jts.2013.18.1.1] [Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.1.1]